Low-level jets drive the summer intra-seasonal variability of the Canary upwelling system - Alves, José M. R.; Miranda, Pedro M.A.; Caldeira, Rui M.A. (Frontiers in Marine Science, 2023)
The role of low-level jets in the intra-seasonal variability of the Canary upwelling system during summer is assessed with a fully coupled, high resolution (3km) ocean-atmosphere numerical simulation. Here, low-level jets include the main continental coastal jet, the tip jets of Madeira and the tip-jets of the steep Canary Islands. The coastline shape, orography of northwest Africa and the proximity of Canary islands lead to complex interactions between the jets, that result in strong surface wind intra-seasonal variability on the multiweek time scale. That variability is forced by oscillations in the shape and position of the Azores subtropical anticyclone, through a strong oscillation in the atmospheric boundary layer height. At the coast, coastal-trapped oscillations with a propagation speed, planetary boundary height, offshore extension, and surface pressure compatible with a Kelvin wave occasionally propagate northward, against the synoptic scale surface pressure. While similar processes have already been observed in California, the mechanisms here described appear to result from interactions of continental coastal processes with a set of steep islands close to the coast. The sensitivity of these dynamics to climate change is a challenging question.